2016
DOI: 10.15376/biores.11.2.5285-5298
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Thermally Modified Southern Pine Wood Pretreated with Alkylalkoxysilanes

Abstract: The alkyl-alkoxysilane (AAS) pre-impregnation method and thermal modification were combined to improve the water-related properties of southern yellow pine (Pinus spp.) sapwood. Four types of AAS with varied alkyl chain lengths, including butyltrimethoxysilane (BTMOS), octyltrimethoxysilane (OTMOS), dodecyltrimethoxysilane (DTMOS), and cetyltrimethoxysilane (CTMOS), were used to pre-impregnate wood samples at a concentration of 5% or 15% mass fraction, and the subsequent thermal modification was processed at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Of these signals, only the one at 1034 cm −1 may be evidence of the covalent bonding of silanol condensation products to the hydroxyl groups of cellulose and starch. The others prove that the organosilicon material has deposited on the paper surface but is not necessarily covalently bound with it [ 17 , 26 ]. This is complicated by the fact that some of these key signals overlap with the cellulose and starch spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these signals, only the one at 1034 cm −1 may be evidence of the covalent bonding of silanol condensation products to the hydroxyl groups of cellulose and starch. The others prove that the organosilicon material has deposited on the paper surface but is not necessarily covalently bound with it [ 17 , 26 ]. This is complicated by the fact that some of these key signals overlap with the cellulose and starch spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Most of them are based on reactive aminosilanes [ 8 ] or chlorosilanes [ 9 , 16 ] in organic solvents, which rapidly condense with water, releasing harmful by-products into the environment; therefore, their application in the highly humid environment of paper machines seems to be impossible. The most promising agents are those based on alkoxysilanes [ 13 , 17 ]. Their condensation with water results in relatively harmless aliphatic alcohols as side products, and the progress and equilibrium of this reaction can be controlled by pH buffers and the relative concentration of di-, tri-, and mono functional silanes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…or other mould species. Works by Ahola et al (2002) and Chen et al (2016) revealed that there is no difference in fungal growth between thermally modified wood and untreated wood tested. Further studies by Gobakken and Lebow (2010) showed that thermally modified Scots pine acts similarly to non-modified Scots pine sapwood against fungal attack.…”
Section: Introductionmentioning
confidence: 84%
“…Similarly to previous works, control samples after thermal modification were covered with the mycelia of the A. niger rapidly. In the work of Chen et al (2016), A. niger mycelium covered about 75% of the surface of modified Southern pine sapwood at 180 °C to 200 °C. A similar phenomenon was noticed in the studies by Yilgör and Nami Kartal (2010).…”
Section: Mould Resistancementioning
confidence: 93%
“…Wood thermally treated can be described as a physical-chemical process that change wood anatomy and wood constituents, such cellulose, hemicellulose, lignin and extractives, performing this process under temperature varying between 150 and 280 °C on controlled atmosphere, which can be vacuum, steam or under heated oil (Batista et al, 2016b;Lee et al, 2018;Wikberg and Maunu, 2004), and for a controlled time, improving physical properties reducing shrinkage, permeability and hygroscopicity, increasing dimensional stability (Barboutis and Kamperido, 2019;Batista et al, 2018;Ribeiro et al, 2019). Otherwise, with wood constituents degradation, such as cellulose and hemicellulose, mechanical properties are reduced proportionally with thermal treatment (Chen et al, 2016;Kariz et al, 2016;Kubovský et al, 2020;Lahtela and Kärki, 2014).…”
Section: Introductionmentioning
confidence: 99%